The Effect of Learning Environment and School Culture on Students Learning Achievement at Private Vocational School of Self Development in Padangsidempuan City - Alfi Nura (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
Effect of Learning Environment and School Culture on Students Learning Achievement at Private Vocational School of Self Development in Padangsidempuan City